Validation of Two Portable Instruments to Measure Iron Concentration in Groundwater in Rural Bangladesh (Journal of Health, Population and Nutrition, 2009)
Iron is ubiquitous in natural water sources used around the world for drinking and cooking. The health impact of chronic exposure to iron through water, which in groundwater sources can reach well above the World Health Organization's defined aesthetic limit of 0.3 mg/L, is not currently understood. To quantify the impact of consumption of iron in groundwater on nutritional status, it is important to accurately assess naturally-occurring exposure levels among populations. In this study, the validity of iron quantification in water was evaluated using two portable instruments: the HACH DR/890 portable colorimeter (colorimeter) and HACH Iron test-kit, Model IR-18B (test-kit), by comparing field-based iron estimates for 25 tubewells located in northwestern Bangladesh with gold standard atomic absorption spectrophotometry analysis. Results of the study suggest that the HACH test-kit delivers more accurate point-of-use results across a wide range of iron concentrations under challenging field conditions. Key words: Groundwater; HACH; Iron; Test-kits; Tubewell; Water analysis; Bangladesh doi: 10.3329/jhpn.v27i3.3384 J Health Popul Nutr 2009 Jun;27(3):414-418